ДОСЛІДЖЕННЯ РЕЖИМУ НАПРУГИ В ДАЛЬНІХ ЛІНІЯХ ЕЛЕКТРОПЕРЕДАЧІ ЗМІННОГО СТРУМУ - Т.Л. Кацадзе; Д.В. Настенко; О.М. Панєнко; О.М. Янковська (Праці Інституту електродинаміки Національної академії наук України, 2021)
The charging currents of EHV transmission lines cause the Ferranti effect, which causes an increase in voltage at intermediate points transmission line. The work aims to study the laws of the voltage distribution along the line route and to develop a method for determining the coordinates of a point with extreme voltage. Methodology. Mathematical modeling of long-distance transmission lines in Wolfram Mathematica allowed to form the laws of the voltage distribution along the line and determine the coordinate of the extreme point on the voltage. Results. It is shown that the application of the traditional model of idealized power transmission causes high modeling accu-racy only in the modes of unloaded line and low loads. In the range of medium and high loads, the simulation er-ror reaches unacceptably large values. The paper proposes more accurate models for determining the coordinate of an extreme voltage point: linearized and second- and third-order models. It is shown that the proposed models are characterized by higher accuracy in a wide range of loads. Increasing the degree of the model results in higher accuracy, but is associated with an increase in the cumbersomeness of the mathematical model. It is shown that first and second-order models provide sufficient accuracy for typical designs of 750 kV power transmission lines. It is shown that neglecting the losses on the corona has almost no effect on the accuracy of calculating the coordinates of the extreme point on the voltage, which simplifies the linear calculation model and models of the second and third-order. Originality. Mathematical models of the first, second and third orders have been devel-oped for high-precision determination of the coordinate of a voltage-extreme point along a long-distance trans-mission line. Practical significance. The offered mathematical models are intended for application in problems of regulation and adjustment of parameters of flexible power transmissions. Ref. 12, figure, tables 4.